CFD analysis of heat transfer enhancement in impinging jet array by varying number of jets and spacing - Zakia Rachdi; Nidhal Hnaien; Aboulbaba Eladeb; Badr M. Alshammari; Lioua Kolsi; Hacen Dhahri (Scientific Reports)
Abstract Using the RANS approach with the standard k-ω turbulence model, this study offers a novel investigation into the dynamic and thermal properties of turbulent impinging jet arrays. Our study examines the combined effect of the number of jets (N) and the jet–jet spacing (S) on flow mechanisms and heat transfer performance, which is unique compared to previous research that frequently focuses on the individual effects of parameters. Through the investigation of the turbulent kinetic energy, friction coefficient, velocity contours, streamlines, pressure contours, and local and mean Nusselt numbers, we provide important information about how these parameters impact flow dynamics. Local heat transfer in the central and lateral zones is greatly improved by increasing the number of jets (N) and the jet–jet spacing (S), according to our findings. When the jet–jet spacing (S) is increased from 1 to 4, the maximum value of the Nusselt number along the central zone improves by 21.2%. Furthermore, the best improvement in the maximum Nusselt number (24.5%) along the lateral zone is obtained by increasing the number of jets (N) from 5 to 11 for the lower value of jet–jet spacing S = 1. It has also been noted that lower jet-plate distance (H), lower jet–jet spacing (S), and a higher number of jets (N) result in better average heat transfer. To predict the average Nusselt number based on three parameters (N, S, and H), we establish a critical correlation, which provides a useful tool for optimizing impinging jet configurations in a variety of engineering applications. The diversification of the parameters studied and the thorough analysis in this study add important new results to the field by demonstrating the significant effects of the number of jets, jet–jet spacing, and jet-plate distance on the thermal and dynamic behavior of impinging jet arrays.